The clinical effectiveness of patient initiated clinics for patients with chronic or recurrent conditions managed in secondary care: a systematic review. - Rebecca Whear; Abdul-Kareem Abdul-Rahman; Kate Boddy; Jo Thompson-Coon; Mark Perry; Ken Stein (PLoS ONE)
Background Missed or inappropriate hospital appointments cost the UK National Health Service millions of pounds each year and delay treatment for other patients. Innovative methods of appointment scheduling that are more flexible to patient needs, may improve service quality and preserve resources. Methods A systematic review of the evidence for the clinical effectiveness of patient initiated clinics in managing long term care for people with chronic or recurrent conditions in secondary care. Seven databases were searched including MEDLINE, Embase and PsycINFO (using the OVID interface), the Cochrane Library of Systematic Reviews and CENTRAL, Science Citation Index Expanded, Social Sciences Citation Index, and Conference Proceedings Citation Index (via the Web of Science interface) from inception to June 2013. Studies comparing patient initiated clinics with traditional consultant-led clinics in secondary care for people with long term chronic or recurrent diseases were included. Included studies had to provide data on clinical or resource use outcomes. Data were extracted and checked by two reviewers using a piloted, standardised data extraction form. Results Eight studies (n = 1927 individuals) were included. All were conducted in the UK. There were few significant differences in clinical outcomes between the intervention and control groups. In some instances, using the patient initiated clinics model was associated with savings in time and resource use. The risk of harm from using the patient initiated clinic model of organising outpatient care is low. Studies with longer follow-up periods are needed to assess the long term costs and the ongoing risk of potential harms. Conclusions The UK policy context is ripe for evidence-based, patient-centred services to be implemented, especially where the use of health care resources can be optimised without reducing the quality of care. Implementation of patient initiated clinics should remain cautious, with importance placed on ongoing evaluation of long term outcomes and costs.